Servicios hospitalarios y su relación con la calidad de atención al usuario del hospital sagrado corazón de jesus. cantón Quevedo, año 2020 - Gilces Jimenez, Linn Narcisa (2023)
User perception depends to a large extent on the quality of care provided in hospital services, where internal management is important for user satisfaction. For this reason, the quality of care in a health institution plays a leading role in its institutional image. For the above reasons, it is necessary to conduct a research, whose objective is to evaluate the hospital services of the Hospital Sagrado Corazón de Jesús in the city of Quevedo and its relationship with the quality of user care. The methodology used in this study consists of the application of deductive and inductive methods, and the Servqual model was also considered to analyze the quality of care provided to the user of medical services. The types of research used are: qualitative-quantitative, correlational, non-experimental, field and cross-sectional. Likewise, the techniques used are the interview and a survey based on the Servqual model, which are aimed at the people who attend the medical institution and representatives of the health center who work in the administrative, medical, quality and statistical areas. The sample considered in the research is 384, of which 382 correspond to citizens who require medical services and the remaining 2 are collaborators of the Sacred Heart of Jesus Hospital